Optimalisasi Komunikasi Internal dan Eksternal Humas Polresta Deli Serdang terhadap Kejahatan Siber - Syahputra, Romi; Kholil, Syukur (Medan Resource Center, 2024)
The rise of cybercrime in Indonesia has become an urgent issue, not only in terms of technical law enforcement but also in how institutions, particularly the police, communicate with the public. This study aims to examine the strategic role of the Public Relations Division (Humas) at Polresta Deli Serdang in managing internal coordination and external communication in response to digital crime. Using a qualitative case study approach, the research involved in-depth interviews with eight key informants and thematic analysis of the collected data. The findings reveal that Humas is often excluded from the early stages of operations, weakening its ability to build narratives that uphold institutional legitimacy. Externally, the public perceives the police as slow and overly formal, failing to match the speed and emotional tone of social media discourse. The study recommends a shift from one-way, bureaucratic communication to a symmetrical approach rooted in local culture, involving digital community leaders and co-created narratives. These findings contribute to strengthening police communication strategies through empathetic, transparent, and collaborative engagement to rebuild public trust.